Colorectal cancer screening: The surgery rates they are a-changing. A nationwide study on surgical resections in Italy. Issue 2 (February 2019) - Zorzi, Manuel; Gennaro, Nicola; Capodaglio, Giulia; Urso, Emanuele Damiano Luca; Pucciarelli, Salvatore; Memo, Laura; Carpin, Eva; Corti, Mariachiara; Rugge, Massimo; Fedeli, Ugo
Abstract: Background: Growing evidence suggests that colorectal cancer (CRC) screening based on the fecal immunochemical test (FIT) reduces CRC incidence and surgical resection rates. Aims: To compare trends in surgery for proximal and distal CRC among Italian regions at different stages of screening implementation. Methods: From the National Hospital Discharge Database we selected hospitalizations with CRC resection of residents aged 50–74 years during 2002–2014, and computed surgery rates for the 8 most populous Italian regions with/without a screening program. Results: In regions with screening, implemented around 2006–2007, the annual percent change (APC) of distal CRC resection was +1.7 (95% confidence interval −1.0, 4.4) during 2002–2007 and −9.1 (−10.6, −7.7) during 2007–2014. No significant change was observed in regions without screening. The APC for proximal colon resection in regions with screening was +5.8 (2.5, 9.0) during 2002–2007 and −4.1 (−5.8, −2.4) during 2007–2014, while in regions without screening surgical rates increased through the whole study period. Compared to 2002, in 2014 distal CRC resection rates were greatly reduced in regions with screening, reaching values similar to proximal CRC resection. Conclusion: Following the implementation of screening programs surgery rates steeply decreased, confirming the deep impact of FIT-based screening on the burden of CRC.